PENYELESAIAN SENGKETA HARTA BERSAMA YANG MELEKAT PADA HARTA BAWAAN (Studi Kasus Pengadilan Agama Polewali Mandar) - Syafriani Azzahra Suzaen; Patimah; Muh. Jamal Jamil (Universitas Islam Negeri Alauddin Makassar, 2023)
Indonesia is a state of law. In the 1945 Constitution Article 1 Paragraph 3 which reads that the State of Indonesia is a state of law which implies that all orders in the life of the nation, society and state are based on applicable law. The rule of law adopted by Indonesia is a rule of law that always considers all actions on two grounds. That is, in terms of its use and purpose and in terms of its legal basis. As a country based on law, all people’s lives are regulated by law regarding matters including marriage, divorce, and the division of property. Marriage is an activity intended to form a family as a legal bond according to law. However, marriage does not only concern the individual husband and wife but also concerns all family and community affairs. In essence, marriage is something sacred, therefor every religion cannot be separated from the rules of marriage and religious principles. Join assets have been explained in Article 35 Paragraph (1) of the marriage law, which explains that property acquired during marriage becomes joint property. Based on the article, joint property only includes property acquired by husband an wife during marriage. Property acquired outside of the marriage period is not joint property.